Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

First dinosaur remains from Serbia: Sauropod and theropod material from the uppermost Cretaceous (Maastrichtian) of Osmakovo - Zoran Marković; Miloš Milivojević; Richard J. Butler; Paul M. Barrett; Simon Wills; Andrew A. van de Weerd; Wilma Wessels; Predrag Radović (Cretaceous Research, 2025)

All the light we cannot see: Climate manipulations leave short and long‐term imprints in spectral reflectance of trees - Artur Stefanski; Ethan E. Butler; Laura J. Williams; Raimundo Bermudez; J. Antonio Guzmán Q.; Andrew Larson; Philip A. Townsend; Rebecca Montgomery; Jeannine Cavender‐Bares; Peter B. Reich (Ecology, 2025)
Anthropogenic climate change, particularly changes in temperature and precipitation, affects plants in multiple ways. Because plants respond dynamically to stress and acclimate to changes in growing conditions, diagnosing quantitative plant‐environment relationships is a major challenge. One approach to this problem is to quantify leaf responses using spectral reflectance, which provides rapid, inexpensive, and nondestructive measurements that capture a wealth of information about genotype as well as phenotypic responses to the environment. However, it is unclear how warming and drought affect spectra. To address this gap, we used an open‐air field experiment that manipulates temperature and rainfall in 36 plots at two sites in the boreal‐temperate ecotone of northern Minnesota, USA. We collected leaf spectral reflectance (400–2400 nm) at the peak of the growing season for three consecutive years on juveniles (two to six years old) of five tree species planted within the experiment. We hypothesized that these mid‐season measurements of spectral reflectance capture a snapshot of the leaf phenotype encompassing a suite of physiological, structural, and biochemical responses to both long‐ and short‐time scale environmental conditions. We show that the imprint of environmental conditions experienced by plants hours to weeks before spectral measurements is linked to regions in the spectrum associated with stress, namely the water absorption regions of the near‐infrared and short‐wave infrared. In contrast, the environmental conditions plants experience during leaf development leave lasting imprints on the spectral profiles of leaves, attributable to leaf structure and chemistry (e.g., pigment content and associated ratios). Our analyses show that after accounting for baseline species spectral differences, spectral responses to the environment do not differ among the species. This suggests that building a general framework for understanding forest responses to climate change through spectral metrics may be possible, likely having broader implications if the common responses among species detected here represent a widespread phenomenon. Consequently, these results demonstrate that examining the entire spectrum of leaf reflectance for environmental imprints in contrast to single features (e.g., indices and traits) improves inferences about plant‐environment relationships, which is particularly important in times of unprecedented climate change.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

The way “urbanization” is defined has strong implications for its effects on mammal abundance - Mairi K.P. Poisson; Fikirte Gebresenbet; Andrew R. Butler; Patrick Tate; Daniel H. Bergeron; Remington J. Moll (Urban Ecosystems, 2024)

Use of multiple climate change scenarios to predict future distributions of alligator gar (Atractosteus spatula) in the United States - Jory Bartnicki; Richard A. Snow; Andrew T. Taylor; Christopher J. Butler (Environmental Biology of Fishes, 2024)

Developing a mealybug pheromone monitoring tool to enhance IPM practices in New Zealand vineyards - Nicola J. Sullivan; Vaughn A. Bell; Ruth C. Butler; Roger Wallis; Remya Ramesh; D. Srinivasa Reddy; Andrew M. Twidle; Barry Bunn; C. Rikard Unelius; Lee-Anne M. Manning; David M. Suckling (Journal of Pest Science, 2023)
Mealybugs are phloem-feeding insects found on many crops worldwide. In New Zealand vineyards, they transmit the economically important Grapevine leafroll-associated virus 3 (GLRaV-3). For some mealybug species, synthetic sex pheromones have been commercialised, and are used as monitoring tools. The mealybugs Pseudococcus longispinus and Pseudococcus calceolariae are major pests in many New Zealand vineyards. We present work on the development of a combined P. longispinus and P. calceolariae pheromone lure. The optimal dose for monitoring P. longispinus was found to be 10 µg of the ( S )-(+)-enantiomer, either alone or in the racemic mixture. Addition of the corresponding alcohol did not improve trap catch of P. longispinus . Both the P. longispinus and the P. calceolariae pheromone lures remained active in the field for 90 days. Combining the 2 species’ pheromones had no negative effects on male mealybug trap catch for either species. We conclude that the pheromone ester alone is the best lure for the male P. longispinus . Combining the two mealybug species’ pheromones into a single lure provides the New Zealand viticultural industry with an efficient monitoring tool. Late-vintage deployment of baited lures will provide information on mealybug abundance and local distribution that will inform the scope of future insecticide programmes, to target areas based on need rather than an area-wide application by default.

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Characterizing observed surface wind speed in the Hudson Bay and Labrador regions of Canada from an aviation perspective - Andrew C. W. Leung; William A. Gough; Ken A. Butler; Tanzina Mohsin; Micah J. Hewer (International Journal of Biometeorology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Dynamics of Large Corporate Forestland Ownerships in the United States - Emma M Sass; Marla Markowski-Lindsay; Brett J Butler; Jesse Caputo; Andrew Hartsell; Emily Huff; Amanda Robillard (Journal of Forestry, 2021)
Ownership of forestland in the United States has changed in recent decades, including the proliferation of timber investment management organizations (TIMOs) and real estate investment trusts (REITs), with the potential to alter forest management and timber supply. This article quantifies forest ownership transitions among ownership categories between 2007 and 2017 and investigates how and why large corporate ownerships own and manage their forestlands. Ownership transitions were determined from refined USDA Forest Service, Forest Inventory and Analysis data; we also conducted a survey of large corporate forestland ownerships. Corporate forestland acreage increased between 2007 and 2017, while family and public forestland decreased. Large corporate landowners report multidimensional, financially focused land management, although industry, timber investment management organizations, real estate investment trusts, and other owners report some different motivations and income streams. This work provides a baseline to track future ownership transitions and the behaviors of large corporate forestland owners.

Metal ions and graphene-based compounds as alternative treatment options for burn wounds infected by antibiotic-resistant Pseudomonas aeruginosa - Nathalie Karaky; Andrew Kirby; Andrew J. McBain; Jonathan A. Butler; Mohamed El Mohtadi; Craig E. Banks; Kathryn A. Whitehead (Archives of Microbiology, 2020)
Burn infections caused by Pseudomonas aeruginosa pose a major complication in wound healing. This study aimed to determine the antimicrobial effect of metal ions, graphene (Gr), and graphene oxide (GO), individually and in combination, against the planktonic and biofilm states of two antimicrobially resistant clinical strains of P. aeruginosa each with different antibiotic resistance profiles. Minimum inhibitory, minimum bactericidal, and fractional inhibitory concentrations were performed to determine the efficacy of the metal ions and graphene composites individually and their synergy in combination. Crystal violet biofilm and XTT assays measured the biofilm inhibition and metabolic activity, respectively. Molybdenum, platinum, tin, gold, and palladium ions exhibited the greatest antimicrobial activity (MIC = 7.8–26.0 mg/L), whilst GO and Gr demonstrated moderate-to-no effect against the planktonic bacterial cells, irrespective of their antibiograms. Biofilms were inhibited by zinc, palladium, silver, and graphene. In combination, silver–graphene and molybdenum–graphene inhibited both the planktonic and biofilm forms of the bacteria making them potential candidates for development into topical antimicrobials for burns patients infected with antibiotic-resistant P. aeruginosa .

Biophysical connectivity explains population genetic structure in a highly dispersive marine species - Nathan K. Truelove; Andrew S. Kough; Donald C. Behringer; Claire B. Paris; Stephen J. Box; Richard F. Preziosi; Mark J. Butler (Coral Reefs, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Reliability of negative BOLD in ipsilateral sensorimotor areas during unimanual task activity - Keith M. McGregor; Atchar Sudhyadhom; Joe Nocera; Ari Seff; Bruce Crosson; Andrew J. Butler (Brain Imaging and Behavior, 2015)

Recent environmental change and trace metal pollution in World Heritage Bathurst Harbour, southwest Tasmania, Australia - Krystyna M. Saunders; Jennifer J. Harrison; Edward C. V. Butler; Dominic A. Hodgson; Andrew McMinn (Journal of Paleolimnology, 2013)

Motor map reliability and aging: a TMS/fMRI study - Keith M. McGregor; Haley Carpenter; Erin Kleim; Atchar Sudhyadhom; Keith D. White; Andrew J. Butler; Jeffrey Kleim; Bruce Crosson (Experimental Brain Research, 2012)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Variability of motor potentials evoked by transcranial magnetic stimulation depends on muscle activation - Warren G. Darling; Steven L. Wolf; Andrew J. Butler (Experimental Brain Research, 2006)

Genetic mapping of a major gene affecting onion bulb fructan content - John McCallum; Andrew Clarke; Meeghan Pither-Joyce; Martin Shaw; Ruth Butler; Don Brash; John Scheffer; Ian Sims; Sjaak van Heusden; Masayoshi Shigyo; Michael J. Havey (Theoretical and Applied Genetics, 2006)

Mirror apraxia affects the peripersonal mirror space. A combined lesion and cerebral activation study - Ferdinand Binkofski; Andrew Butler; Giovanni Buccino; Wolfgang Heide; Gereon Fink; Hans-Joachim Freund; Rdiger J. Seitz (Experimental Brain Research, 2003)